2021
DOI: 10.3390/molecules26164886
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Antioxidant and Anti-Inflammatory Activities of Selected Plant Compounds and Their Metal Ions Complexes

Abstract: Numerous plant compounds and their metal-ion complexes exert antioxidative, anti-inflammatory, anticancer, and other beneficial effects. This review highlights the different bioactivities of flavonoids, chromones, and coumarins and their metal-ions complexes due to different structural characteristics. In addition to insight into the most studied antioxidative properties of these compounds, the first part of the review provides a comprehensive overview of exogenous and endogenous sources of reactive oxygen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 336 publications
(440 reference statements)
1
62
0
Order By: Relevance
“…Recently, as a part of microbiotherapy, indole and its derivates were extensively explored in terms of antifungal, anti-platelet, and antioxidant effects in various diseases ( Mucha et al, 2021 ). Accumulating shreds of evidence have demonstrated that indole and its derivatives derived from the intestine exert a profound effect on the intestinal barrier function and intestinal immunity ( Alexeev et al, 2018 ; Scott et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as a part of microbiotherapy, indole and its derivates were extensively explored in terms of antifungal, anti-platelet, and antioxidant effects in various diseases ( Mucha et al, 2021 ). Accumulating shreds of evidence have demonstrated that indole and its derivatives derived from the intestine exert a profound effect on the intestinal barrier function and intestinal immunity ( Alexeev et al, 2018 ; Scott et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as a part of microbiotherapy, indole and its derivates were extensively explored in terms of antifungal, anti-platelet, and antioxidant effects in various diseases (Mucha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Catechin (Figure 1), a flavan-3-ol, is an extensively investigated flavonoid that commonly occurs in many popular beverages and foods, such as green tea, cocoa, dark chocolate, apples, grapes, and others [34]. Due to its antioxidant properties, catechin shows anti-inflammatory [35,36], and cardio- [35,37] and neuroprotective [35,38] effects. Controversially, catechin was also investigated for possible allelopathic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The two review articles in this Special Issue presented an overview of the information available on two important topics [ 6 , 7 ]. The first is a comprehensive up-to-date review focused on natural compounds and their complexes, exhibiting a broad spectrum of pharmacological activities, and the second one deals with research on and the applications of platinum-based drugs.…”
mentioning
confidence: 99%
“…The review by Budzisz et al [ 6 ] highlighted the beneficial biological activities of plant compounds and their metal complexes, which are attributable to their different structural characteristics and substitution patterns. The first part of the review provides a comprehensive overview of exogenous and endogenous sources of reactive oxygen and nitrogen species, oxidative stress-mediated damage of lipids and proteins, and the protective roles of antioxidant defense systems, including plant-derived antioxidants.…”
mentioning
confidence: 99%